2009
DOI: 10.1149/1.3207569
|View full text |Cite
|
Sign up to set email alerts
|

Pitting Behavior of Passivated Cadmium Monocrystals

Abstract: A combination of aqueous thermodynamics, anodic polarization tests, and scanning electron microscopy was used to study the pitting behavior of Cd monocrystals in a phosphate-buffered (pH 11.2) solution of 0.1 M NaCl. Pitting occurred in the passive region where the most stable passive film was Cd(OH)2 . The film thickness was estimated to be ∼4×10−9m . Pitting potentials were not reproducible, being variable within surfaces of the same orientation and between different orientations. Variability was attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(59 reference statements)
1
3
0
Order By: Relevance
“…We observed that the dendrites were mainly aligned along the basal plane for each of the grain orientations. This is similar to the orientation-dependent pitting corrosion in Cd 25 and Mg. 28,29 Although the details of the kinetics of pitting and negative dendrite formation are different, we attribute our dendrite orientations to the same cause as that observed in the pitting corrosion of elemental Cd and Mg -the anisotropy of surface energy. In the hcp structure, the basal plane has the lowest surface energy.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…We observed that the dendrites were mainly aligned along the basal plane for each of the grain orientations. This is similar to the orientation-dependent pitting corrosion in Cd 25 and Mg. 28,29 Although the details of the kinetics of pitting and negative dendrite formation are different, we attribute our dendrite orientations to the same cause as that observed in the pitting corrosion of elemental Cd and Mg -the anisotropy of surface energy. In the hcp structure, the basal plane has the lowest surface energy.…”
Section: Resultssupporting
confidence: 79%
“…Mg 0.10 Cd 0.90 , which was also electropolished in H 3 PO 4 -glycol-water (2:2:1 in volume ratio) solution. 25 Dealloying of Mg was performed in ionic liquids (iLs); either a Choline Chloride (ChCl) and Urea eutectic mixture (ChCl-Urea) or 1-Butyl-3-MethylImidazoliumm bis-Trifluoromethylsulfonate (BMImTfSI) (EMD chemicals), ChCl-Urea was prepared by mixing ChCl (Alfa Aesar, 95+%) and Urea (EMD chemicals, 99%) in 1:2 molar ratio. Prior to the electrochemical experiments, both iLs were de-aerated in an MBraun glove box.…”
Section: Methodsmentioning
confidence: 99%
“…7 ). It can be seen that the CV curve exhibits several redox peaks, indicating that the capacitance is mainly governed by the pseudocapacitor behaviour based on the redox process, as following: 31 CdO + H 2 O + OH − + e − ↔ Cd(OH) 3 − Cd(OH) 3 − + OH − + e − ↔ Cd(OH) 4 2− …”
Section: Resultsmentioning
confidence: 99%
“…147, 149 and 150) are not stable in highly acidic or alkaline electrolytes or reductive potentials, as they form soluble species. 147,150 Regarding CdS [151][152][153] and also CdTe, 154 Cd dissolves in highly acidic and alkaline electrolytes, 155 and is thermodynamically stable only at signicant cathodic overpotentials, not attained without applied bias. Cu-based photoabsorber (CIS, CIGS, CZTS, .)…”
Section: Small Band Gap Semiconductors Corrosion Examples In Aqueous Electrolytesmentioning
confidence: 99%